PENGARUH MEDIA QUIZIZZ TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS - Jois Syahadati Masruriyah; Mira Azizah; Qoriati Mushafanah (STKIP Subang, 2023)
This study aims to determine the effect of the quizizz learning media on the mathematical communication skill of first grade students of SD Supriyadi 02 Suemarang. The type of research used is a Quantitative Pre-Experimental Research type One-Group Pretest-Posttest Design. The sampling technique used was saturated sampling. Sampling in this study were first grade A students of SD Supriyadi 02 Semarang with a total of 29 students consisting 0f 15 boys and 14 girls as the experimental class. Data collection uses pretest-posttest description questions. The data analysis technique in this study used the Shapiro-Wilk analysis prerequisite test and the hypothesis test used the Wilcoxon test because the data were not normally distributed. The results using the Wilcoxon test show that the significance value (2-tailed) is 0.000 on both test question which means Ha is accepted. So it can be concluded that the use of the quizizz learning media has an effect on the mathematical communication skills of first grade A students of SD Supriyadi 02 Semarang.